Analisis Layout Warehouse Bahan Baku Menggunakan Sistem First In First Out Pada PT Toso Industry Indonesia - Bukhori Al Fizikri; Heni Rohaeni; Indah Rizki Maulia (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study analyzes the raw material warehouse layout of PT Toso Industry Indonesia by applying the First In First Out (FIFO) system. An inefficient warehouse layout can cause disruptions in material flow, inefficient space utilization, and difficulties in raw material distribution. Using a qualitative comparative case study approach, this research compares the current warehouse layout with a proposed layout that is more efficient. The findings indicate that the current layout is still suboptimal in implementing the FIFO method, which hinders inventory management effectiveness. The proposed layout offers significant improvements in operational efficiency with a more structured workflow.